An Annotated list of the alien plants of urban flora of Mykolayiv (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The list of alien plants of urban flora of Mykolayiv includes 244 species from 171 genera, 56 families, 2 classes, 1 divisio.
Keywords: urban flora, Mykolayiv, alien plants, an annotated list.